PERANAN PENDIDIKAN JASMANI DALAM MEMBENTUK KEDISIPLINAN SISWA MADRASAH ALIYAH NEGERI 2 BANDA ACEH - Safrizal (Jurnal Penjaskesrek, 2022)
Physical education is a part of overall education that prioritizes physical activity and fostering a healthy life for physical, mental, social and emotional growth and development in harmony, in balance. As for what must be considered in physical education, namely the purpose of physical education, the function of physical education, and the benefits of physical education. The method in this study uses a descriptive method which aims to describe the symptoms that occur in the present. The population in this study were students of class X Madrasah Aliya Negeri 2 Banda Aceh totaling 180 students. The sampling technique was carried out by means of purposive sampling with a total of 27 people. Data collection techniques in this study through questionnaires and documentation. The data analysis used the level category with the aim of getting the level of discipline at Madrasah Aliya Negeri 2 Banda Aceh and then calculating the percentage. The results of data analysis are as follows: (1) as many as 0 respondents are in the low category with a percentage level of 0%, (2) as many as 6 respondents are in the medium category with a percentage level of 20.78% and (3) as many as 21 respondents are in the high category with a percentage rate of 79.23%. From the results of this study it can be concluded that the role of physical education is needed in shaping student discipline at Madrasah Aliya Negeri 2 Banda Aceh.AbstrakPendidikan jasmani adalah suatu bagian dari pendidikan keseluruhan yang mengutamankan aktivitas jasmani dan pembinaa hidup sehat untuk pertumbuhan dan perkembangan jasmani, mental , sosial, dan emosional yang serasi, selaras seimbang. Adapun yang harus diperhatikan dalam pendidikan jasmani yaitu tujuan pendidikan jasmani, fungsi pendidikan jasmani, dan manfaat pendidikan jasmani. Metode pada penelitian ini menggunakan metode deskriptif yang bertujuan mendeskripsikan gejala-gejala yang terjadi pada masa sekarang. Populasi dalam penelitian ini adalah siswa kelas X Madrasah Aliya Negeri 2 Banda Aceh berjumlah 180 jumlah siswa. Teknik pengambilan sampel yang dilakukan dengan cara Purposive sampling dengan jumlah 27 orang. Teknik pengumpulan data dalam penelitian ini melalui kuesioner dan dokumentasi. Analisis data menggunakan kategori jenjang dengan tujuan untuk mendapatkan tingkat kedisiplinan Madrasah Aliya Negeri 2 Banda Aceh dan selanjutnya menghitung persentase. Hasil analisis data sebagai berikut: (1) sebanyak 0 responden berada pada kategori rendah dengan tingkat persentase 0%, (2) sebanyak 6 responden berada pada kategori sedang dengan tingkat persentase 20,78% dan (3) sebanyak 21 responden berada pada kategori tinggi dengan tingkat persentase 79,23%. Dari hasil penelitian ini dapat disimpulkan bahwa peranan pendidikan jasmani sangat dibutuhkan dalam membentuk kedisiplinan siswa di Madrasah Aliya Negeri 2 Banda Aceh